Global market for veterinary herbal products during the 2018-2019 period - Rodríguez Coipel, Yudit; Domínguez Odio, Aníbal; Mena Álvarez, Odaimis; Toirac Proenza , Raiselys; González Marrero , Isbel; Cala Delgado, Daniel Leonardo (Brazilian Journal of Veterinary Research and Animal Science, 2021)
The industrial manufacturing of natural products for veterinary use represents a major weakness in the veterinary sector despite increased interest and the traditional ancestral knowledge that supports them. A cross-sectional, descriptive observational study was conducted to characterize the veterinary herbal products marketed worldwide during 2018 and 2019. A comprehensive thematic search limited to the 2018-2019 period was performed in the ScienceDirect, Scopus, PubMed, Web of Science, ResearchGate, and Academic Search Complete databases. The investigation identified 487 products registered in the global market manufactured by 54 companies, led by India, The Netherlands, and the United Kingdom. The market segments of animal production and phytomedicines were dominant with 73.7% and 53.0% of products, respectively. Cattle (22.2%), sheep-goats (16.2%), and canines (16.2%) were the most favored species. The most represented therapeutic indications were those intended to treat gastrointestinal disorders (30.47%), antimicrobials (16.66%), and antiparasitic agents (10.47%). The families Fabaceae, Lamiaceae, Asteraceae, Apiaceae, Malvaceae, and Rutaceae stood out because of their frequent use, encompassing 35.0% of the 137 declared species. Andrographis paniculata (Burm.f.) Nees and Withania somnifera (Lin) Dunal were the most important species. Oral formulations for internal use (72%) and liquids (51%) in 100 mL, 500 mL, and 1 L presentations showed the highest prevalence on the market. The global market for veterinary herbal products during the 2018-2019 period was relevant in the productive and medical animal sector. No differences were found between medicinal plant species used to formulate herbal products for human and animal use.